Determinants of economic growth in Honduras: Regression analysis - Villela, Roldan; Paredes, Juan Jacobo (The Economics and Finance Letters, 2025)
This research aims to evaluate the relationship between various determinants of economic growth and real GDP in Honduras from 1990 to 2020. Using regression analysis across four groups (models) of determinants, this study employs time series data extracted from World Bank online databases. The first model, focused on economic sectors comprising GDP according to the value-added method, reveals that industry, services, and agriculture have a positive and significant relationship with real GDP. The second model, covering key determinants, indicates that only infrastructure and labor force show a positive and significant relation with economic growth. The third model, focusing on education, shows a positive and significant correlation between tertiary school enrollment and real GDP, while primary school enrollment exhibits a negative and significant correlation with economic growth. The fourth model encompasses non-economic determinants, with findings revealing that Voice and Accountability, Political Stability, and Rule of Law have a negative and significant relationship with economic development, whereas Government Effectiveness and Control of Corruption are positively and significantly associated with economic growth. Overall, most determinants prove inconsequential or show a negative relationship with economic growth. The findings highlight the complexity of fostering economic growth in Honduras, where traditional growth factors like education and governance show varied effects. Strategic investments in tertiary education, infrastructure, and institutional effectiveness could drive positive outcomes. These insights suggest that growth strategies in Honduras and similar contexts require targeted, multifaceted approaches.